The Effect of Corporate Social Responsibility (CSR), Firm Size, Profitability, Leverage and Earning Persistence on Company Value - Novia Dwi Lestari; Ika Yustina Rahmawati; Wida Purwidianti; Hermin Endratno (Indonesian Journal of Business Analytics, 2024)
The study aims to test the effect of CSR, firm size, profitability, leverage and earning persistence on company value. The study was conducted primary consumer companies in food and beverage subsector listed in Indonesian Stock Exchange in the period 2019-2022. Sample selection in this study used the method of purposive sampling and obtained 25 samples. Data used in research is quantitative obtained from secondary data using unbalance data. Test results using the SPSS 26 analytical tool. This study shows that CSR variables, firm size, and earnings persistence have no effect on company value, while profitability and leverage variables have a positive effect on company value. This research contributes to corporate management on the importance of company value in the business.